Effect of gallium arsenide technology on the formation of integrated circuit structures - Новосядлий, Степан Петрович; Мельник, Любомир Васильович (Eastern-European Journal of Enterprise Technologies, 2014)
Despite the apparent success of silicon technology, further development of the modern electronics industry will heavily depend on the development of new materials interfaces, in particular, gallium arsenide (semiconductor structures based on compounds ). Some characteristics of devices made from these materials have great advantages (e.g. high-speed performance and compatibility with light and laser diodes), but the technology of forming the structures is very sensitive to the properties of the semiconductor interface. These interface properties at the atomic level can determine the types of the microelectronic and optoelectronic devices and circuitry based on them, which can be made on the basis of such semiconductor materials. Electrical properties are one of the most important aspects of the interface. Electrical characteristics of the interface are defined by the relative placement of electronic levels on both sides of the interface, the electronic states at the interface itself and the interface behavior under the action of the applied voltage, current and temperature. For example, in the metal-semiconductor contact systems (MSC) the position of the Fermi level in metal towards the edge of the conduction band and valence band of the semiconductor is an important parameter that determines the height of the Schottky barrier and the volt-ampere characteristic (VAC). At the same time, for the ohmic contacts the voltage loss at the metal-semiconductor interface at high-level current injection must be very small.